Circadian rhythm and heart disease - what is the link? A review - Agnieszka Brzezińska; Aleksandra Skorupa; Aleksandra Nowińska; Justyna Nowaczek (Kazimierz Wielki University, 2022)
Introduction and purpose: Cardiovascular disease (CVD) is still the leading cause of death worldwide and causes 49% of mortality in Europe. This makes CVD is the most important reason for premature mortality and Disability Adjusted Life Years ("DALYS") in that continent. It is associated with variables such as blood pressure, heart rate, circulating catecholamines, markers of blood coagulation and vascular endothelial function which are dependent on different times of the day. The epidemiological data indicate that the biggest number of CVD incidents occur during the early morning hours. In this work we try to discuss the circadian rhythm and its impact on variables which, according to data, are most crucial on CV incident rate. Brief description of the state of knowledge: The cardiovascular disease and mortality risk is associated with variables such as morning blood pressure, fluctuations in metabolism rate or even in immunological response. These variables are dependent on the circadian rhythm. This article covers the most crucial components affected by the daily fluctuations considering the heart according to the literature from the last five years.  Conclusions: This review highlighted the link between circadian rhythm and cardiovascular disease with the purpose of focusing on the most important clinically aspects of that machinery from blood pressure to inflammation. Despite all of these exciting findings which could possibly have future implications in the field of cardiology, there is still a significant need to explore this complicated relationship between the biological clock and the heart.